Pruning to Improve Flowering and Fruiting of ‘Crystal’ Guava - Susanto, Slamet; Melati, Maya; Aziz, Sandra Arifin (AGRIVITA, Journal of Agricultural Science, 2019)
Pruning is one of the techniques to improve plant growth and production. The aim of this research was to determine the effect of pruning on vegetative and generative growth, and fruit quality of ‘Crystal’ guava. The experiment was conducted from September 2016 to April 2017 at Cikabayan Research Station of Bogor Agricultural University, Dramaga, Bogor, Indonesia (-6.550780, 106.714531). The experiment used completely randomized design with six replications. There were three treatments i.e. a) pruning by leaving 4 pairs of leaves, b) pruning by leaving 8 pairs of leaves, and c) control (without pruning). Pruning was applied after shoot leaves grew fully. The result showed that pruning significantly increased the total number of shoots and generative shoots. Pruned plants produced more flower and fruit than un-pruned ones. Pruning by leaving 4 pairs of leaves tended to produce higher number of flower and fruit than those by leaving 8 pairs of leaves. Fruit weight and internal fruit quality were not affected by pruning.